18FDG-PET/CT for predicting the outcome in ER+/HER2- breast cancer patients: comparison of clinicopathological parameters and PET image-derived indices including tumor texture analysis. Issue 1 (December 2017) - Groheux, David; Martineau, Antoine; Teixeira, Luis; Espié, Marc; de Cremoux, Patricia; Bertheau, Philippe; Merlet, Pascal; Lemarignier, Charles
Abstract Background This study investigated the value of some clinicopathological parameters and 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography (18 FDG-PET/CT) indices, including textural features, to predict event-free survival (EFS) in estrogen receptor-positive/human epidermal growth factor receptor 2-negative (ER+/HER2-) locally advanced breast cancer (BC) patients. Methods FDG-PET/CT indices and clinicopathological parameters were assessed before neoadjuvant chemotherapy (NAC). After completion of chemotherapy, all patients had breast surgery with axillary lymph node dissection, followed by radiation therapy and endocrine therapy for 5 years. EFS was estimated using the Kaplan-Meier method. A Cox proportional hazard regression model was used for multivariate analysis. Results One hundred forty-three consecutive patients with stage II–III ER+/HER2- BC and without distant metastases at baseline PET were included. High standardized uptake values (SUVs), were associated with shorter EFS (HR = 3.51, P <  0.01 for SUVmax ; HR = 2.76, P =  0.02 for SUVmean ; and HR = 4.40P  < 0.01 for SUVpeak ). Metabolically active tumor volume (MATV, HR = 3.47, P <  0.01) and total lesion glycolysis (TLG, HR = 3.10, P <  0.01) were also predictive of EFS. Homogeneity was not predictive (HR = 2.27, P =  0.07) and entropy had weak prediction (HR = 2.89, P =  0.02). Among clinicopathological parameters, EFS was shorter in progesterone receptor (PR)-negative tumor (vs. PR-positive tumor; HR = 3.25, P <  0.01); histology was predictive of EFS (lobular vs. ductal invasive carcinoma; HR = 3.74, P =  0.01) but not tumor grade (grade 3 vs. grade 1–2; HR = 1.64, P  = 0.32). Pathological complete response after NAC was not correlated to the risk of relapse. Three parameters remained significantly associated with EFS in multivariate analysis. MATV (HR = 1.01, P  < 0.01), progesterone receptor expression (HR = 2.90, P =  0.03) and tumor histology (HR = 3.80, P =  0.02). Conclusions Baseline PET parameters measured before neoadjuvant treatment have prognostic values in ER+/HER2- locally advanced breast cancer patients. After multivariate analysis, metabolically active tumor volume remains significant while textural analysis of PET images is not of added value. Considering histopathological parameters, our study shows that patients with PR-negative or lobular invasive tumor have poorer prognosis than patients with PR-positive or ductal carcinoma, respectively.